Collaboration between Local Government, Schools, and Community in an Effort to Eradicating Quranic Illiteracy through The Sekolah Mengaji Program in Bandung Regency - Rust, Rustina; Kosasih, Aceng; Fakhruddin, Agus (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Quranic illiteracy is a serious challenge in many communitues, affecting religious understanding and practice. This study aims to analyze the Collaboration between Local Government, Schools, and Communities in an Effort to Eradicating Quranic Illetracy Through the Sekolah Mengaji Program in Bandung Regency. This study used a descriptive qualitative methode involving research subjects consisting of documents from the local government, PAI teachers, students, and quran recitation teachers at SDN Cangri and SDN Magung 3. The data collection techniques were document study, interviews, and field observations. This research identifies the role of each party in the implemtation of the program. The result show that the local government has commited by allocating a budget and setting standards for Sekolah Mengaji teachers. School function as education providers that integrate religious values into the curriculum, while the community participates in supporting learning activities, both as parents and as communiti members. While the program shows potential for succes in reducing qur’an illiteracy still need to be overcome. The conclution of this study emphasizes the importance of Collaboration berween Local Government, Schools and Communities in creating a more qualified generation in the field off religious education in Bandung Regency.